KERUSAKAN DINDING SEL Escherichia coli OLEH MINYAK ATSIRI TEMU KUNCI (Kaempferiapandurata) - Miksusanti, Miksusanti; Jennie, Betty Sri Laksmi; Ponco, Bambang; Trimulyadi, Gatot (Research Center for Biology-Indonesian Institute of Sciences, 2008)
Antibacterial activity of temu kunci (Kaempferiapandurata) essential oil against Escherichia coli Kl.l was analyzed. Activity of antibacterial essential oil was analyzed through its ability to leak the Escherichia coli Kl.l cell wall and altering it.Minimum Inhibitory Concentration (MIC) of temu kunci essential oil is 0.11% (v/v). Further studies were conducted using the concentration of 1 MIC and 2 MIC.Leakage phenomena were monitored with atomic adsorption spectrometry (AAS), and ultraviolet spectrophotometry(UV).Alteration of cell wall was analyzed with scanning electron microscopy (SEM).The optical density values observed by UV spectrophotometer for protein and nucleic acid leakage were 0.3813-0.6573 at 280 nm and 0.2186-0.5603 at 260 nm.The result showed that K. pandurata essential oil could leak the inorganic ion Ca 17-53%, and K* 9-43% from the bacteria and alter the cell wall of the bacteria.